Live mulch: a new approach to weed control and crop production in the tropics - Akobundu, I. (1980)
Live mulch is a crop production technique in which a food crop is planted directly in a living cover of an established cover crop without tillage or destruction of the fallow vegetation. The effect of several established legume covers on weed competition, fertilizer requirement and yield of maize was studied in the field at the International Institute of Tropical Agriculture. Weed infestation was heaviest in unweeded conventionally tilled and no-tillage plots, but very low in unweeded Centrosema pubescens and Psophocarpus palustris plots. Consequently, maize yield was reduced in all ground covers where weed infestation was heavy but not in the covers that effectively suppressed weeds. Maize yield was significantly higher in the live mulch plots that received no fertilizer than in similarly treated conventionally tilled and no-tillage plots. When 60 kg/ha each of N, P2O5 and K2O was applied to all ground covers, maize yield in the live mulch plots was either equal to or better than in the conventionally tilled and no-tillage plots.